Integration Of Digital Transformation, Social Competencies, And Innovative Thinking In The Development Of Accounting And Auditing Systems In New Uzbekistan (Eurasian Journal of History, Geography and Economics, 2026)
This research is devoted to the urgent issues of fundamentally improving the accounting and auditing system in the context of the modernization of the economy of New Uzbekistan. The main objective of the study is to scientifically substantiate the mechanisms for integrating digital technologies, social competencies of specialists, and the paradigm of innovative thinking. The article highlights the influence of digital transformation drivers such as Artificial Intelligence (AI) and Big Data analytics on audit quality and transparency. Furthermore, the role of soft skills and professional ethics in shaping the profile of the modern auditor is analyzed, and new priorities for human capital development are identified. The author proposes a synergistic development model for the accounting and auditing sector and justifies its practical significance. The conclusions and recommendations developed in the study aim to increase the international competitiveness of financial system specialists and ensure the sustainability of the national economic reporting system.